Maternal depression and adverse neighbourhood conditions during pregnancy are associated with gestational epigenetic age deceleration. Issue 13 (9th December 2022) - Appleton, Allison A.; Lin, Betty; Kennedy, Elizabeth M.; Holdsworth, Elizabeth A.
ABSTRACT: Gestational epigenetic age (GEA) acceleration and deceleration can indicate developmental risk and may help elucidate how prenatal exposures lead to offspring outcomes. Depression and neighbourhood conditions during pregnancy are well-established determinants of birth and child outcomes. Emerging research suggests that maternal depression may contribute to GEA deceleration. It is unknown whether prenatal neighbourhood adversity would likewise influence GEA deceleration. This study examined whether maternal depression and neighbourhood conditions independently or jointly contributed to GEA deceleration, and which social and environmental neighbourhood conditions were associated with GEA. Participants were from the Albany Infant and Mother Study (n = 204), a prospective non-probability sampled cohort of higher risk racial/ethnic diverse mother/infant dyads. GEA was estimated from cord blood. Depressive symptoms and census-tract level neighbourhood conditions were assessed during pregnancy. Maternal depression (β = −0.03, SE = 0.01, p = 0.008) and neighbourhood adversity (β = −0.32, SE = 0.14, p = 0.02) were independently associated with GEA deceleration, controlling for all covariates including antidepressant use and cell type proportions. Neighbourhood adversity did not modify the association of maternal depression and GEA (β = 0.003, SE = 0.03, p = 0.92). igher levels of neighbourhood poverty, public assistance, and lack of healthy food access were each associated with GEA deceleration; higher elementary school test scores (an indicator of community tax base) were associated with GEA acceleration (all p < 0.001). The results of this study indicated that maternal depression and neighbourhood conditions were independently and cumulatively associated GEA in this diverse population.